Calprotectin in Chronic Inflammatory Demyelinating Polyneuropathy and Variants—A Potential Novel Biomarker of Disease Activity - Frauke Stascheit (Frontiers in Neurology, 2021)
Background: In chronic inflammatory demyelinating polyneuropathy (CIDP), there is an urgent need for biomarkers to monitor ongoing disease activity. Serum calprotectin (CLP) induces signaling pathways involved in inflammatory processes and has been shown to correlate with markers of disease activity in other autoimmune disorders. Thus, we wanted to study the potential value of CLP in comparison to serum neurofilament light chain (sNfl) to monitor disease activity.Materials and Methods: Sera from 63 typical and atypical CIDP and 6 MMN patients with varying degrees of disease activity were analyzed in comparison with 40 healthy controls (HC) in a cross-sectional design. Association of CLP and sNfl levels with socio-demographics, disease duration, CIDP disease activity scale (CDAS), and impairment status [medical research council-sum score (MRC-SS), the inflammatory neuropathy cause and treatment disability score (INCAT-DS), grip strength, and maximum walking distance], patient-reported outcome (PRO) parameters [SF-36 questionnaire, Beck's depression index (BDI), and fatigue severity scale (FSS)], as well as treatment regime were investigated using uni- and multivariate analysis.Results: CLP and sNfl levels were significantly higher in all CIDP patients compared to HC (p = 0.0009). Multivariate analysis adjusted for age and gender revealed that CLP acts as an independent predictor for CIDP and MMN. CLP was significantly associated with active disease course according to CDAS and correlated with MRC-SS, whereas sNfl correlated with parameters of disease impairment. There was no correlation with PRO, except for sNfl and the mental health composite score. Subgroup analysis revealed no differences between typical CIDP and atypical variants.Conclusions: CLP was elevated in CIDP and variants and was associated with active disease course, whereas sNfl shows further potential as biomarker of axonal degeneration. Thus, CLP might be a suitable additive biomarker for measurement of ongoing inflammation, which is greatly needed to guide better patient care in CIDP.